2021
DOI: 10.3390/jintelligence9040056
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Emotional Intelligence Discourse on Social Media: Insights from the Analysis of Twitter

Abstract: Social networks have created an information diffusion corpus that provides users with an environment where they can express their views, form a community, and discuss topics of similar or dissimilar interests. Even though there has been an increasingly rising demand for conducting an emotional analysis of the users on social media platforms, the field of emotional intelligence (EI) has been rather slow in exploiting the enormous potential that social media can play in the research and practice of the framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Opinion dynamics refer to how people's views change over time through interactions with one another. Opinion dynamics is a multidisciplinary research field that attracts scientists from different domains and has been applied to diverse fields, including social psychology [17], politics [18], physics [19], internet network sciences [20], business management [21], and more.…”
Section: Opinion Dynamics Modelsmentioning
confidence: 99%
“…Opinion dynamics refer to how people's views change over time through interactions with one another. Opinion dynamics is a multidisciplinary research field that attracts scientists from different domains and has been applied to diverse fields, including social psychology [17], politics [18], physics [19], internet network sciences [20], business management [21], and more.…”
Section: Opinion Dynamics Modelsmentioning
confidence: 99%
“…In contrast to potential biases in questionnaires and interviews, Internet social media provides real-time insights into emotions, capturing a diverse range of voices for better representativeness. Social media platforms such as Weibo (Wei-dong, 2018) and Twitter (Shardul, 2021) provide opportunities for users to express emotions in real-time. Ruoyu (2022) explored the relationship between emotions and greenery using Weibo text data and found that higher levels of visible greenery were associated with lower negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…As Slovaks love social media (Flintham et al, 2018;Levitskaya & Fedorov, 2020), there is a presumption that the credibility of the population concerning conspiracies in the social media space will increase (Vosoughi, Roy & Aral, 2018;Zhou & Zafarani, 2020). In addition, as a result of increasing misinformation and fake news (UNESCO, 2021; Khan, Michalas & Akhunzada, 2021;Bakir & McStay, 2018;Bradshaw & Howard, 2018;Fitzpatrick, 2018), it is also expected that social media will become even more to disseminate reports favoring political polarization (closely linked to emotionality in politics) (Tucker et al, 2018;Corbu & Negrea-Busuioc, 2020;Osmundsen, 2021;Serrano-Puche, 2021), as well as the use of social networks in the dissemination of diverse emotional discourses (Shankar & Tewari, 2021;Richards, 2011;Ott, 2017;Allcott & Gentzkow, 2017). Already today, it turns out that these preconditions meet.…”
Section: Introductionmentioning
confidence: 99%